Pengaruh Soft Skill dan Hard Skill pada Mahasiswa Tingkat Akhir Program Studi Akuntansi Terhadap Kesiapan Kerja Studi Kasus pada Generasi Z di Kota Denpasar - Putu Wulan Karnia Dewi; Putu Sri Arta Jaya Kusuma (AKUNTANSI 45, 2024)
This research purposes is as a tool for analyze the influence both of soft skills and hard skills on work alertness, especially in the generation Z who are the successors of the nation. This research used explanatory methods and quantitative approaches. The samples that used for this research were 36 Gen-Z samples. The technique used for data collection for this research was from survey questions using the Likert Scale's method. The sampling method used probability with a measurement technique using simple random sampling. The final result of this research is that in path analysis it can be recapitulate that Soft Skills (X1) have a positive impact and significant effect on Work Alertness (Y) with a greater t-value. from the t-table (4.082 > 2.011) and level of significant (0.000 < 0.05). Meanwhile, Hard Skill (X2) have a positive impact and significant effect on Work Alertness (Y) with the t-calculated and the t-table value, where the t-calculated have more value than the t-table value (3.082 > 2.011) and level of significant is (0.001 < 0.05).